Penempatan Plang (Signage) Desa pada Decision Point Pengunjung Desa Kambingan - Akhmad Andi Saputra; Ikhtisholiyah Ikhtisholiyah; Hasti Suprihatin; Adi Mulya Kusuma (Jurnal Pengabdian Pada Masyarakat METHABDI, 2025)
The village has potential natural resources in agriculture and aquaculture ponds. Potential agriculture and pond systems use a rainfed system to irrigate rice fields and ponds. In addition, Kambingan Village already has a permanent irrigation network. The Cerme people certainly know how to reach Kambingan Village, but those from outside the Cerme Subdistrict need clear signage to avoid missing it when visiting. The type of road pavement entering the village is divided into 2 (two) types, namely paving pavement and asphalt pavement. The condition of the asphalt pavement is good, while the condition of the paving pavement is bumpy. The activity method in community service in Kambingan Village is the science and technology simulation method, where students redesign signage using design applications to create design concepts and engineering equipment for the fabrication and installation of signage. The stages carried out include identifying problems in the field, coordinating with the village chief, redesigning the signage board, fabricating the signage board, removing the old signage board, and installing new signage at a point determined by the village chief. The expected result is that the community receives information on directions to enter Kambingan Village through the installation of a new signage board, and that the road shoulder from Cerme District to Benjeng District gains color or character.